Methodological Approaches To The Development Of Regional Food Supply Systems With Account For Their Influence On The Food Market - Mikhail A. ANANIEV (Communications of International Proceedings, 2021)
The article discusses about methodological approaches to the development of regional food supply systems with account for their influence on the food market. The cornerstone of any national food supply system is the resources of its regions. What is meant is the natural and climatic, material and technical, socio-economic potential of the constituent entities of the Russian Federation. Their account in the control system is possible both as separate objects or its independent elements, as well as an aggregate of those. In general, they represent a single organizational and resource basis for the national food supply system. The article provides interesting interpretations of various aspects of this issue.
Keywords: Food Supply System; Resource Potential; Regional Differentiation.